(untitled) (Advancements in Homeopathic Research, 2025)
Introduction: Liver dysfunction, including sluggish liver and fatty liver disease, poses a growing global health challenge, exacerbated by lifestyle factors and hepatotoxic exposures. Conventional therapies offer relief but are often limited by side effects, prompting increased interest in complementary hepatoprotective remedies. Alpha™-Liv Sugar Free Liver Tonic- a multi-ingredient homeopathic tonic, is known for its efficacy in management of liver diseases in diabetic patients. This study aimed to evaluate the real world effectiveness and safety of Alpha™-Liv Sugar Free Liver Tonic in managing functional hepatic disturbances. Methods & Methods: A post-marketing survey was conducted using a structured Google Form distributed to physicians across India. Data was collected on speed of action, clinical effectiveness, and adverse effects based on physicians’ experience with Alpha™- Liv Sugar Free Liver Tonic. Responses from 80 prescribing doctors were analyzed using descriptive statistics. Results: Of the respondents, 90% rated Alpha™-Liv Sugar Free Liver Tonic effectiveness between 4 and 5, indicating high therapeutic benefit. Over 93.75% observed symptomatic improvement within a week. A favorable safety profile was reported by 98.75% of physicians, with negligible adverse effects noted. Conclusion: Alpha™-Liv Sugar Free Liver Tonic demonstrates strong clinical acceptance for its effectiveness and rapid action in liver dysfunction management. Its multi-targeted homeopathic formulation and high tolerability make it a promising option in integrative hepatology.